2014
DOI: 10.1016/j.bbmt.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Priming with Recombinant Human Granulocyte Colony–Stimulating Factor on Conditioning Regimen for High-Risk Acute Myeloid Leukemia Patients Undergoing Human Leukocyte Antigen–Haploidentical Hematopoietic Stem Cell Transplantation: A Multicenter Randomized Controlled Study in Southwest China

Abstract: HLA-haploidentical hematopoietic stem cell transplantation (haplo-HSCT) is an effective and immediate treatment for high-risk acute myeloid leukemia (HR-AML) patients lacking matched donors. Relapse remains the leading cause of death for HR-AML patients after haplo-HSCT. Accordingly, the prevention of relapse remains a challenge in the treatment of HR-AML. In a multicenter randomized controlled trial in southwestern China, 178 HR-AML patients received haplo-HSCT with conditioning regimens involving recombinant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 32 publications
0
17
1
Order By: Relevance
“…Recently, an encouraging report from China showed that there was a lower relapse rate and better survival in patients treated with G-CSFecombined conditioning compared with those without G-CSF in haploidentical SCT for high-risk AML [36]. Although a decreased relapse rate was observed in our previous report of CBT for de novo AML [20], G-CSFecombined conditioning was not associated with a decreased risk of relapse in MDS and sAML in this study.…”
Section: Discussioncontrasting
confidence: 66%
“…Recently, an encouraging report from China showed that there was a lower relapse rate and better survival in patients treated with G-CSFecombined conditioning compared with those without G-CSF in haploidentical SCT for high-risk AML [36]. Although a decreased relapse rate was observed in our previous report of CBT for de novo AML [20], G-CSFecombined conditioning was not associated with a decreased risk of relapse in MDS and sAML in this study.…”
Section: Discussioncontrasting
confidence: 66%
“…Recently, Gao, et al reported that there was a lower relapse rate and better survival in patients treated with G-CSF-combined conditioning compared to those without G-CSF in haploidentical HSCT for high-risk AML [24]. These data suggested that G-CSF-combined conditioning reduced the posttransplant relapse rate by enhancing the anti-leukemia effect without increasing the chemotherapy dose.…”
Section: Discussionmentioning
confidence: 96%
“…Haploidentical donors can safely extend transplantation options for AML patients without HLA matched siblings or unrelated donors [156,157]. HLA-haploidentical HSCT is an effective and immediate therapeutic modality for high-risk AML patients who lack matched donors [158]. The use of fractionated 800 cGy-TBI-based conditioning therapy and unmanipulated peripheral blood stem cell grafts seems feasible and can result in favorable outcomes for adult patients with AML in CR undergoing haploidentical HSCT [159].…”
Section: Allogeneic Hsct For Amlmentioning
confidence: 99%
“…The use of fractionated 800 cGy-TBI-based conditioning therapy and unmanipulated peripheral blood stem cell grafts seems feasible and can result in favorable outcomes for adult patients with AML in CR undergoing haploidentical HSCT [159]. However, relapse remains a leading cause of death in high-risk AML patients subjected to haploidentical HSCT [158]. Achievement of CR before transplantation and recombinant human G-CSF priming of conditioning therapy can improve the outcome of patients with high-risk AML receiving haploidentical allografts [158,160].…”
Section: Allogeneic Hsct For Amlmentioning
confidence: 99%
See 1 more Smart Citation